2021
DOI: 10.1186/s12967-021-02812-7
|View full text |Cite
|
Sign up to set email alerts
|

HDAC4 induces the development of asthma by increasing Slug-upregulated CXCL12 expression through KLF5 deacetylation

Abstract: Background Asthma is a frequently occurring respiratory disease with an increasing incidence around the world. Airway inflammation and remodeling are important contributors to the occurrence of asthma. We conducted this study aiming at exploring the effect of Histone deacetylase 4 (HDAC4)-mediated Kruppel-like factor 5 (KLF5)/Slug/CXC chemokine ligand-12 (CXCL12) axis on the development of asthma in regulation of airway inflammation and remodeling. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…160 In a mouse model of ovalbumin (OVA)-induced asthma, HDAC4 was upregulated in the lung tissue. 161 We and others have also shown that inhibition of endogenous HDAC activity reconstitutes the defective barrier by increasing TJ expression. 55,159,[161][162][163] https://doi.org/10.2147/JAA.S324080…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 90%
See 1 more Smart Citation
“…160 In a mouse model of ovalbumin (OVA)-induced asthma, HDAC4 was upregulated in the lung tissue. 161 We and others have also shown that inhibition of endogenous HDAC activity reconstitutes the defective barrier by increasing TJ expression. 55,159,[161][162][163] https://doi.org/10.2147/JAA.S324080…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 90%
“…161 We and others have also shown that inhibition of endogenous HDAC activity reconstitutes the defective barrier by increasing TJ expression. 55,159,[161][162][163] https://doi.org/10.2147/JAA.S324080…”
Section: Genetic and Epigenetic Changes In Bronchial Epitheliummentioning
confidence: 90%
“…HDAC2 protein expression could be reduced by cigarette smoke exposure via enhancing AKT signaling, and it can be reversed by roxithromycin (RMX) treatment to increase HDAC2 expression and reduce airway inflammation ( 159 ). The expression of HDAC4 was upregulated in lung tissues of asthmatic mice, and it could deacetylate Kruppel-like factor 5 (KLF5) to upregulate Slug and CXC chemokine ligand-12 (CXCL12), thus triggering airway remodeling and promoting progression of asthma ( 26 ). Overexpression of SIRT6 reduced cell migration and proliferation, suppressed the activation of Smad3 phosphorylation induced by TGF-β1 treatment, and at the same time decreased the H3K9 acetylation level and the transcriptional activity of the c-Jun promoter ( 160 ).…”
Section: Histone Modifications In Inflammatory Diseasesmentioning
confidence: 99%
“…The association of these transcription factors with asthma was demonstrated. For example, histone deacetylase 4 can mediate KLF5 deacetylation to upregulate CXCL12, leading to airway remodeling and promoting the progression of asthma ( 42 ).…”
Section: Resultsmentioning
confidence: 99%